Re-architecture parameters and recommendatory guidelines in adaptive reuse for local open-air architectural museums - Singson, Manuel Agustin Z.
An emergent demand in preserving cultural heritage specifically architectural wealth in the country brought about an emerging studies and practice in conservation and restoration. Varied options and approaches have been considered in implementing such projects which involves delicate materials and structural aspects of these heritage buildings. Procedures and guidelines have been established using international standards that are widely accepted in the field from the basic documentation and existing condition analysis, to design interventions under the premise of adaptive reuse and redevelopment. Many heritage buildings and houses around the country have been 'converted' into open-air museums as a repository and showcase the community's cultural wealth and traditions. This thesis will deliberate on existing case studies such as Taal in Batangas, Vigan in Ilocos and Sagada, Mountain Province which fall into different adaptive reuse categories as an open-air architectural museum. The substance of this research will tackle the theory and practice of adaptive reuse. Standards and guidelines from UNESCO, ICCROM, ICOMOS, Venice and Burra Charters and the Hoi-An Protocol of adaptive reuse implemented all over the world are reviewed to extract suitable parameters that coincides with the data gathered in the field research. As a product, this thesis drafted initial recommendatory guidelines for Sagada using the identified material and immaterial parameters.